2019
DOI: 10.1097/md.0000000000014907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allisartan isoproxil on blood pressure and target organ injury in patients with mild to moderate essential hypertension

Abstract: Evidence has shown that angiotensin II type 1 receptor antagonists have lower blood pressure and have target organ protective effects, but this is not the case for the drug allisartan isoproxil. The aim of this study was to evaluate the effects of allisartan isoproxil on blood pressure and target organ injury in patients with mild to moderate essential hypertension. In total, 80 essential hypertensive participants were randomly divided into an allisartan group and a nifedipine group (n = 40 per grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Allisartan isoproxil is a new nonpeptide angiotensin II receptor blocker precursor drug. Compared with losartan, allisartan isoproxil has higher absorption efficiency, better blood pressure lowering effect and lower adverse reactions ( 25 , 26 ). In the present study, it was revealed that treatment of DCM with allisartan isoproxil in diabetic rats alleviated inflammation and oxidative stress injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allisartan isoproxil is a new nonpeptide angiotensin II receptor blocker precursor drug. Compared with losartan, allisartan isoproxil has higher absorption efficiency, better blood pressure lowering effect and lower adverse reactions ( 25 , 26 ). In the present study, it was revealed that treatment of DCM with allisartan isoproxil in diabetic rats alleviated inflammation and oxidative stress injury.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, increased levels of Ang II have been reported to regulate the production of ROS and lead to cardiac hypertrophy, left ventricular dysfunction, and myocardial insulin resistance ( 22 , 23 ). Allisartan isoproxil is a new nonpeptide angiotensin II receptor blocker (ARB) precursor drug that can produce a carboxylic acid derivative (EXP3174) during absorption in vivo ( 24 , 25 ). Compared with losartan, allisartan isoproxil can be completely hydrolysed by esterase into the active metabolite EXP3174 after being absorbed into the small intestine and stomach ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…It stimulates cellular hypertrophy [ 12 ], protein synthesis, activation of NADPH oxidase system to generate ROS [ 13 ] and synthesize collagen in the vascular smooth muscle cells [ 14 ]. Reduction of cardiovasular events was reported with blockade of the RAS [ 15 , 16 ]. Several antihypertensive agents including angiotensin II receptor blockers (ARBs) and angiotensin-converting enzyme (ACE) inhibitors acts by blocking the RAS and are widely used in the management of hypertension [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Losartan, an orally active ARB is widely used due to its well-established efficacy and safety profile in hypertensive patients [ 15 , 23 ]. In humans, cytochrome P450 (CYP450) metabolizes losartan to various metabolites along with an active carboxylic acid metabolite, EXP3174 that includes around 14 % of losartan [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation